Access to a Labile Monomeric Magnesium Radical by Ball‐Milling. Issue 15 (18th February 2022) - Jędrzkiewicz, Dawid; Mai, Jonathan; Langer, Jens; Mathe, Zachary; Patel, Neha; DeBeer, Serena; Harder, Sjoerd
Abstract: In order to isolate a monometallic Mg radical, the precursor (Am)MgI⋅(CAAC) (1 ) was prepared (Am= t BuC(N‐DIPP)2, DIPP=2, 6‐diisopropylphenyl, CAAC=cyclic (alkyl)(amino)carbene). Reduction of a solution of 1 in toluene with the reducing agent K/KI led to formation of a deep purple complex that rapidly decomposed. Ball‐milling of 1 with K/KI gave the low‐valent Mg I complex (Am)Mg⋅(CAAC) (2 ) which after rapid extraction with pentane and crystallization was isolated in 15 % yield. Although a benzene solution of 2 decomposes rapidly to give Mg(Am)2 (3 ) and unidentified products, the radical is stable in the solid state. Its crystal structure shows planar trigonal coordination at Mg. The extremely short Mg−C distance of 2.056(2) Å indicates strong Mg−CAAC bonding. Calculations and EPR measurements show that most of the spin density is in a π* orbital located at the C−N bond in CAAC, leading to significant C−N bond elongation. This is supported by calculated NPA charges in 2 : Mg +1.73, CAAC −0.82. Similar metal‐to‐CAAC charge transfer was calculated for M 0 (CAAC)2 and [M I (CAAC)2 + ] (M=Be, Mg, Ca) complexes in which the metal charges range from +1.50 to +1.70. Although the spin density of the radical is mainly located at the CAAC ligand, complex 2 reacts as a low‐valent Mg I complex: reaction with a I2 solution in toluene gave (Am)MgI⋅(CAAC) (1 ) as the major product. Abstract : Ball‐milling of a magnesium iodide precursor with K/KI gave a mononuclear Mg radical which is stabilized by a CAAC ligand. Although stable in the crystalline state, the complex decomposed rapidly in solution. According to calculations and EPR spectroscopy, most of the spin density is localized on the CAAC ligand.